Zein-based Nanocarriers as Potential Natural Alternatives for Drug and Gene Delivery: Focus on Cancer Therapy - Elzoghby, Ahmed; Freag, May; Mamdouh, Hadeer; Elkhodairy, Kadria (Current Pharmaceutical Design, 2017)
Protein nanocarriers possess unique merits including minimal cytotoxicity, numerous renewable sources, and high drug-binding capability. In opposition to delivery carriers utilizing hydrophilic animal proteins, hydrophobic plant proteins (e.g, zein) have great tendency in fabricating controlled-release particulate carriers without additional chemical modification to stiffen them, which in turn evades the use of toxic chemical crosslinkers. Moreover, zein is related to a class of alcohol-soluble prolamins and generally recognized as safe (GRAS) carrier for drug delivery. Various techniques have been adopted to fabricate zein-based nanoparticulate systems including phase separation coacervation, spray-drying, supercritical anti-solvent approach, electrospinning and self-assembly. This manuscript reviews the recent advances in the zein-based colloidal nano-carrier systems such as nanospheres, nanocapsules, micelles and nanofibers with a special focus on their physicochemical characteristics and drug delivery applications.
Keywords: nano-carrier